Ben Jervis, Chris Briggs, Alice Forward, Tomasz Gromelski and Matthew Tompkins, The Material Culture of English Rural Households, c. 1250–1600 - Stone, David (Medieval Settlement Research, 2024)
Book review of The Material Culture of English Rural Households, c. 1250–1600.